Thoracic epidural spinal angiolipoma with coexisting lumbar spinal stenosis: Case report and review of the literature - Benvenutti-Regato, Mario (Int J Spine Surg, 2015)
BACKGROUND: Spinal angiolipomas (SALs) are uncommon benign lesions that may present insidiously with back pain or acutely with weakness due to tumor bleeding/thrombosis. Given their rarity, these lesions are often overlooked in the differential diagnosis of epidural masses. The purpose of this article is to report the case of an epidural SAL and to conduct a literature review on the topic. METHODS: A case report and review of the literature using the PubMed/Medline databases. All case reports and case series were reviewed up to June 2015. RESULTS: A 65-year old female presented with neurogenic claudication and magnetic resonance imaging (MRI) revealed lumbar spinal stenosis. Following decompressive surgery, she experienced symptom resolution, but three months postoperatively she presented to the emergency department with acute paraparesis. A thoracic MRI revealed a lesion located between T8 and T10 causing severe spinal cord compression. Following emergent laminectomy and en bloc resection, the patient regained function and the lesion was diagnosed as SAL. Our literature review revealed 178 reported cases, with a female and thoracic predominance. The majority of patients underwent surgical treatment, achieving a gross total resection in most cases. Similarly, complete symptom resolution was the most common outcome. CONCLUSION: Spinal angiolipomas are uncommon spinal tumors. However, they may be treated as any other space-occupying lesion, and surgical resection allows for complete symptom recovery in most patients.